PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI ( Studi empiris pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2013-2016 ) - Afidah Ainul Lathifah, 14.05.52.0119; Aini, Nur (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the effect of Liquidity, Profitability and Leverage to the value of companies with dividend policy as moderation variable. The population in this study is manufacturing company listed on the Indonesia Stock Exchange in 2013-2016. Sampling method using purposive sampling with the number of 225 companies that can be processed. Data analysis technique used is Moderated Regression Analysis Test. The results of this indicate that liquidity has positive and not significant effect to the value of the company. Profitability has a significant positive effect on company value. Leverage has positive and not significant effect to the value of company. Dividend policy have negative and not significant effect on company value. The dividend policy is not able to significantly moderate the effect of liquidity on company value. The dividend policy is capable of significantly moderating the effect of profitability on company value. The dividend policy is not able to significantly moderating the effect of leverage on company value. Keywords: Liquidity, Profitability, Leverage, Dividend Policy, Company Value